Efficacy and safety of neoadjuvant immunotherapy combined with chemotherapy for stage II–IVa esophageal cancer: a network meta-analysis - Mingxing Wang; Wanhui Dong; Gongyi Wu; Baorui Zhang; Tong Lai; Aixin Liu; Qingming Sun (Systematic Reviews)
Abstract Objective The objective of this study was to evaluate the clinical efficacy and safety of neoadjuvant immunochemotherapy in the treatment of locally advanced, resectable esophageal cancer. Methods Literature published before November 2023 on the clinical efficacy and safety of neoadjuvant immunotherapy in resectable esophageal squamous cell carcinoma was searched in CNKI, VIP, Wanfang, Chinese Biomedical Literature, PubMed, Embase, Cochrane, and the Web of Science. A meta-analysis was conducted using Stata 17.0. Results The cumulative ranked probability results indicated that Camrelizumab + TN had the highest probability of achieving pCR, Camrelizumab + TP of achieving MPR, and Sintilimab + TP of achieving DCR and ORR. Camrelizumab + TP also had the highest probability of achieving an R0 resection rate. In terms of adverse events and postoperative complications, Pembrolizumab + TN had the highest likelihood of inducing myelosuppression and rash. Toripalimab + TP had the highest probability of inducing vomiting, while traditional chemotherapy alone had the highest likelihood of inducing postoperative cardiac adverse events. Conclusion Neoadjuvant immunotherapy combined with chemotherapy has demonstrated superior clinical efficacy and safety compared to chemotherapy alone. The regimen of Camrelizumab + TP showed significant advantages in pCR, MPR, DCR, and R0 resection rates, particularly excelling in MPR and R0 resection rates. However, it was associated with a higher incidence of rash compared to chemotherapy alone and the Toripalimab + TP regimen. Neoadjuvant immunotherapy, when combined with chemotherapy, has been shown to reduce the occurrence of postoperative cardiac adverse events. Among the various treatment options, Sintilimab + TP exhibited the most favorable outcomes. Systematic review registration PROSPERO Protocol Number: CRD42024623160.